Manipulation of frozen water droplets with nanoparticles - Sathiasingham Rethinasingam (Nanyang Technological University, 2020)
Nanofluids are colloidal nanoparticles suspended in a base fluid. Nanofluids are widely known to improve energy efficiency through their high thermal conductivity. Various studies have shown that the freezing properties of nanofluids differ from conventional heat transfer fluids. This project is driven by the motivation to study the manipulation of frozen water droplets using nanoparticles. This study aims to gain further insight on the geometrical changes of the frozen droplet using nanoparticles. This study will also show the singularity phenomenon that occurs when freezing deionized water as well as the change in this geometric shape with the effects of nanoparticles. It will be observed that this singular point will be altered to form a flat top with increasing concentrations of nanoparticles. This project will quantify this distinct flat top with dimensionless parameters of the ratio of the top radius to the base width of the frozen droplet, ratio of frozen droplet height to liquid height as well as freezing times. The nanoparticle used in this experiment is Aluminum Hydroxide.